2014
DOI: 10.1074/mcp.m113.034975
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the Chromatin-associated Proteome Identifies HP1BP3 as a Novel Regulator of Cell Cycle Progression

Abstract: The chromatin-associated proteome (chromatome) regulates cellular gene expression by restricting access of transcriptional machinery to template DNA, and dynamic re-modeling of chromatin structure is required to regulate critical cell functions including growth and replication, DNA repair and recombination, and oncogenic transformation in progression to cancer. Central to the control of these processes is efficient regulation of the host cell cycle, which is maintained by rapid changes in chromatin conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 73 publications
4
35
0
Order By: Relevance
“…Functions of Hp1bp3 that have been identified include regulation of chromatin structure (Dutta, et al, 2014), gene expression (Garfinkel, et al, 2015b), cell cycle progression (Dutta, et al, 2014), and insulin signaling (Garfinkel, et al, 2015a), several of which were supported by our analyses. For example, positive correlates of Hp1bp3 were significantly enriched both in nuclear localization (Figure 6a) and insulin signaling (Fig 6b).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Functions of Hp1bp3 that have been identified include regulation of chromatin structure (Dutta, et al, 2014), gene expression (Garfinkel, et al, 2015b), cell cycle progression (Dutta, et al, 2014), and insulin signaling (Garfinkel, et al, 2015a), several of which were supported by our analyses. For example, positive correlates of Hp1bp3 were significantly enriched both in nuclear localization (Figure 6a) and insulin signaling (Fig 6b).…”
Section: Resultssupporting
confidence: 75%
“…A number of studies suggest this family of proteins play a highly specific role in gene expression, possibly due to their role in chromatin organization (Garfinkel, et al, 2015b). It is thought that Hp1bp3 contributes to the inter-conversion of heterochromatin and euchromatin (Dutta, et al, 2014), thereby activating or silencing specific genes as needed. As long-term memory and cognition depend on de novo gene expression in response to a learning and/or training event (Cavallaro, et al, 2002), it is possible that Hp1bp3 is regulating the transcription of specific genes necessary for successful cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…S6A and S6B). Indeed, we have previously demonstrated that HP1BP3 plays an important role in the maintenance of heterochromatin integrity, and that depletion of HP1BP3 increases the MNase sensitivity of chromatin samples (38). Accordingly, our MNase digestion experiments confirmed that hypoxia increased chromatin resistance to nuclease activity, suggesting that these samples contained increased proportions of heterochromatin compaction (Fig.…”
Section: Resultssupporting
confidence: 68%
“…7A). DSB repair by homologous recombination is restricted to the late S and G 2 phases of the cell cycle, whereas NHEJ repair of DSBs can occur throughout interphase (47,48), and our previous analyses of cellcycle-associated changes in the chromatome suggested that NHEJ repair mechanisms operate throughout interphase but are particularly active during G 1 and G 2 (38). Our findings are therefore consistent with the concept that hypoxia induces G 0 -G 1 cycle arrest to enhance NHEJ-mediated repair of DSBs and increase cancer cell resistance to radio-and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…HP1BP3 associates with ERβ in culture (Nassa et al, 2011), binds to chromatin specifically at the repressive histone 3 lysine 9 trimethylation (H3K9me3) mark, and is expressed in most tissues with 10-fold higher levels in the brain (Garfinkel et al, 2015). Knockdown of HP1BP3 by siRNA in culture leads to significant expression changes in hundreds of genes, suggesting it is involved in transcriptional regulation (Dutta et al, 2014;Garfinkel et al, 2015). Interestingly, some genes with the most significantly altered expression in culture experiments are known to mediate progesterone inhibition of estradiol signaling in the uterus, such as MIG-6 (Yoo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%